Kajian Turnover Intention Perawat di RSX Prasetya Husada Malang (Permasalahan dan Penyebabnya) - Faramita, Nanditya Ika; Winarni, Indah; Mansur, Moh. (Jurnal Aplikasi Manajemen, 2015)
Hospital X (RSX) is a D-type hospital that provides general and specialist health services. One of the important human resources in the RSX is nurse. There is a growing percentage of the turnover of nurses in the RSX in 2011-2013 is 10%, 11% and 15% that impact on financial and non-financial aspect in hospital. In the financial aspect, turnover have increased the costs of recruitment and trainning whereas in non-financial areas of hospital services is declining. Evaluation of nurse's turnover can be predicted in an indirect way by examining the turnover intention and examines the problems that arise for nurses working in RSX. This research is qualitative research with case study approach in two key informants and nine additional informants. Data was collected through interviews, observations and documentation of the research setting in the Emergency Room Unit (ERU), Inpatient Internal Medicine and Surgery Room (IIMSR) and the Operating Room (OR). The problems in work that could potentially lead to turnover intention are: high workload, unfair incentives, ambiguity in leadership, lack of appreciation and spatial in IIMSR which makes difficult to work. While problems outside the work situation that could potentially be the cause of turnover intention are bored and the presence of another job offer. The problems that make a great influence to turnover intention of nurses in the RSX are the high workload and lack of appreciation. Workload and lack of appreciation affects turnover intention affect job satisfaction and organizational commitment.